Análise biogeográfica do grupo de gêneros Scotussae, Tribo Dichroplini (Orthoptera: Acrididae: Melanoplinae) do Brasil - Piunti, Ana Laura Navarro (Universidade Federal de São Carlos, 2025)
The Genus Group Scotussae of the Tribe Dichroplini (Orthoptera: Acrididae: Melanoplinae) comprises seven genera of grasshoppers distributed throughout the Neotropical region, with 38 species recorded in Brazil. Given the vast territorial extent of Brazil, there is a continuous biogeographical challenge in precisely delimiting the occurrence and distribution patterns of species, and gaps in this knowledge, as is the case with the species belonging to this Group of Genus recorded in the country. Thus, this work aims to analyze the georeferenced data of species from the Genus Group Scotussae (Tribe Dichroplini) in Brazil, based on consolidated records in the scientific literature and in entomological collection databases. After tabulating this data, the QGIS software was used to create maps of the spatial distribution of the species. This approach allowed us not only to illustrate the distribution, but also to highlight the areas with the highest concentration of records and to delineate the knowledge gaps regarding the biogeography of the genera. The results demonstrated that the distribution of species in this Group of Genera is significantly associated with the Cerrado (60%), Atlantic Forest (47%), and Pampas (34%) biomes, reflecting their ecological preferences and potential relationships with environmental factors. The distribution mapping carried out in this study aims to support future investigations on Scotussae species, assisting in the determination of factors influencing their dispersal, in the identification of potential organisms for bioindication or biological control in Brazil, and providing valuable information for additional taxonomic and ecological analyses.
Biogeographical analysis of the genus group Scotussae, Tribe Dichroplini (Orthoptera: Acrididae: Melanoplinae) from Brazil
Keywords: Biogeografia; Caelifera; Distribuição; Gafanhoto; Mapeamento; Biogeography; Distribution; Grasshopper; Mapping; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES; 15. Vida Terrestre